Factorising Double Brackets Hard

Easy

Medium

Difficult

Q1) \((6x + 4)(2x -4)\)
Q1) \(4 x^2 + 12 x+ 9= \)
Q1) \(9 x^2 -6 x-8= \)
Q2) \((2x + 10)(9x + 3)\)
Q2) \(6 x^2 + 11x+ 4= \)
Q2) \(6 x^2 -17 x+ 12= \)
Q3) \((2x + 6)(3x -7)\)
Q3) \(9 x^2 + 12 x+ 4= \)
Q3) \(6 x^2 -5 x-6= \)
Q4) \((9x + 6)(4x -5)\)
Q4) \(8 x^2 + 22 x+ 5= \)
Q4) \(6 x^2 + x-15= \)
Q5) \((5x + 8)(9x -2)\)
Q5) \(6 x^2 + 11x+ 3= \)
Q5) \(4 x^2 -16 x+ 15= \)
Q6) \((6x + 3)(4x -2)\)
Q6) \(8 x^2 + 14 x+ 3= \)
Q6) \(6 x^2 -11x-10= \)
Q7) \((9x + 8)(10x -3)\)
Q7) \(6 x^2 + 13 x+ 5= \)
Q7) \(6 x^2 + 17 x-14= \)
Q8) \((2x + 8)(2x + 2)\)
Q8) \(6 x^2 + 7 x+ 2= \)
Q8) \(9 x^2 -21x+ 10= \)
Q9) \((6x + 3)(8x -2)\)
Q9) \(6 x^2 + 13 x+ 6= \)
Q9) \(9 x^2 + 6 x-8= \)
Q10) \((10x + 4)(10x -2)\)
Q10) \(6 x^2 + 17 x+ 5= \)
Q10) \(6 x^2 + x-12= \)